Geographic information system-based spatial modelling of soil-transmitted helminth infections among preschool-aged children in Masbate, Philippines - Acepcion, Sarah Joy A.
Since the effectiveness of the Zero Open Defecation (ZOD) program as a scaling-up approach of the Integrated Helminth Control Program (IHCP) in lowering the rates of Soil-Transmitted Helminth (STH) infections for Preschool-Aged Children (PSAC) has not yet been locally explored, this study aimed to (1) describe the association between environmental determinants and STH cumulative prevalence, and (2) to predict the 2020 STH cumulative prevalence among Preschool-Aged Children in the selected municipalities of Masbate based on the statistically significant environmental determinants using ArcGIS Pro's spatial statistics tool.